Black-phosphorus-analogue tin monosulfide: an emerging optoelectronic two-dimensional material for high-performance photodetection with improved stability under ambient/harsh conditions. Issue 36 (22nd August 2018) - Huang, Weichun; Xie, Zhongjian; Fan, Taojian; Li, Jiagen; Wang, Yunzheng; Wu, Leiming; Ma, Dingtao; Li, Zhongjun; Ge, Yanqi; Huang, Ziyin N.; Dai, Xiaoyu; Xiang, Yuanjiang; et al.
Abstract : Black-phosphorus-analogue tin monosulfide was successfully introduced to resolve the instability issue of black phosphorus. Abstract : It is widely known that excellent intrinsic electronic and optoelectronic advantages of black phosphorus (BP) make it attractive for applications in transistor, logic and optoelectronic devices. However, easy degradation upon exposure to ambient conditions turns out to be the most critical bottleneck in restricting its practical applications. In order to simultaneously achieve good stability and high device performance, a two-dimensional (2D) size-selected black-phosphorus-analogue (BPA), tin monosulfide nanosheets (SnS Ns), with enhanced chemical stability was successfully fabricated by a facile liquid phase exfoliation (LPE) method, followed by a liquid cascade centrifugation (LCC) technique. Similar to BP, SnS shows thickness modulated bandgap energy. The as-prepared SnS Ns were employed to fabricate working electrodes for photoelectrochemical (PEC)-type broadband photodetection for the first time, and they exhibit an appropriate capacity for a self-powered broadband photoresponse. More importantly, due to the weak polar character of Sn–S bonds, the SnS-based photodetector shows strong long-term temporal and cycling stability of ON/OFF switching behaviour without any external protection not only in regular basic electrolytes but also under strong polar conditions including harsh acidic and neutral electrolytes. We therefore anticipate that SnS as an emerging optoelectronic material might be developed towards versatile applications such as photodetection, sensing and modulation, etc.